The Chemometrics Techniques in Combination with Instrumental Analytical Methods Applied in Halal Authentication Analysis - Abdul Rohman; Anggita Rosiana Putri (Universitas Gadjah Mada, 2019)
Halal food is taken into account as any food permitted to be consumed by Muslim according to Syariah law. Due to the development of science and technology in which some new food components such as food additives have been synthesized and produced, some industries used non-halal components such as pig derivatives in food products to reduce the production cost. Non-halal components added in food products are difficult to detect visually due to the close similarity between non-halal ingredients and components present in food. As a consequence, some scientists developed and proposed some instrumental techniques like spectroscopy, chromatography and molecular biology-based methods for identification of non-halal components. Food matrix is very complex to be analyzed. Therefore, the signals obtained during chemical and biological analyses are very complex which are difficult to interpret. Fortunately, a statistical technique called with chemometrics can be used an alternative method to handle the complex data met during analysis of non-halal components. Chemometrics has been widely used in many aspects of analysis in many types of the sector. In this review, some chemometrics techniques used to treat responses obtained from instrumental measurements intended for analysis of non-halal components in food matrix were highlighted.